2018
DOI: 10.1016/j.jesp.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Experiential fluency and declarative advice jointly inform judgments of truth

Abstract: Processing fluency, the experienced ease of ongoing mental operations, influences judgments such as frequency, monetary value, or truth. Most experiments keep to-be-judged stimuli ambiguous with regards to these judgment dimensions. In real life, however, people usually have declarative information about these stimuli beyond the experiential processing information. Here, we address how experiential fluency information may inform truth judgments in the presence of declarative advice information. Four experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
55
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 32 publications
11
55
0
1
Order By: Relevance
“…These results fit with previous findings suggesting that fluency affects truth judgments independent of prior knowledge and other factors (Fazio et al, 2015;Unkelbach & Greifeneder, 2018). While participants can, and often do, judge the truth of a statement based on their prior knowledge or source credulity (Begg, Anas, & Farinacci, 1992;Unkelbach & Greifeneder, 2018), they are also influenced by low-level perceptual cues that impact fluency, such as font color and repetition (Reber & Schwarz, 1999;Unkelbach, 2007). Thus, even when participants are given advice on which statements are true or false from an advisor who is described as being 100% accurate, their truth judgements are still affected by repetition (Unkelbach & Greifeneder, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results fit with previous findings suggesting that fluency affects truth judgments independent of prior knowledge and other factors (Fazio et al, 2015;Unkelbach & Greifeneder, 2018). While participants can, and often do, judge the truth of a statement based on their prior knowledge or source credulity (Begg, Anas, & Farinacci, 1992;Unkelbach & Greifeneder, 2018), they are also influenced by low-level perceptual cues that impact fluency, such as font color and repetition (Reber & Schwarz, 1999;Unkelbach, 2007). Thus, even when participants are given advice on which statements are true or false from an advisor who is described as being 100% accurate, their truth judgements are still affected by repetition (Unkelbach & Greifeneder, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, in the same study, there was no evidence that the size of the illusory truth effect was affected by the reliability of the advisor. The increase in perceived truth with repetition was equivalent regardless of whether the advisor was described as being 50, 60, 70, 80, 90 or 100% accurate (Unkelbach & Greifeneder, 2018). Similarly, we found that our results were best explained by a model where all statements show an identical increase as a function of repetition, regardless of plausibility.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Another cue is the source of the information. People are less likely to believe statements that come from unreliable sources (Begg, Anas, & Farinacci, 1992;Unkelbach & Greifeneder, 2018). However, people also rely on other more proximal cues for truth.…”
mentioning
confidence: 99%
“…In fact, people continue to rely on these proximal cues, such as repetition, even when they have access to more direct signals of truth such as prior knowledge and source reliability (Fazio et al, 2015;Fazio et al, 2019;Fazio & Sherry, in press;Unkelbach & Greifeneder, 2018). That is, while people pay attention to cues such as prior knowledge and source credibility when judging truth, they are also affected by proximal cues such as repetition.…”
mentioning
confidence: 99%